ผลลัพธ์การดำเนินการของกองทุนฟื้นฟูสมรรถภาพที่จำเป็นต่อสุขภาพ จังหวัดหนองบัวลำภู: ผลลัพธ์การดำเนินการของกองทุนฟื้นฟูสมรรถภาพที่จำเป็นต่อสุขภาพ จังหวัดหนองบัวลำภู - ปัญหาราช, สุริยันต์ (ASEAN Journal of Rehabilitation Medicine, 2017)
Objectives: To study performance results of the Nongbualamphu Rehabilitation Fund. Study design: Cross Sectional Study. Setting: Nongbualamphu province. Methods: A Questionaire based on the Public Sector Management Quality Award was used as a tool for data collection from 51 Nongbualamphu Rehabilitation Fund committees and official staff. Data were analyzed and reported as frequency, percentage, mean and standard deviation. Pearson Correlation analysis was used to study factors that correlated with performance results of Nongbualamphu Rehabilitation Fund. Results: The Nongbualamphu Rehabilitation Fund self assessment showed excellent level of leadership, strategic planning ,client and stakeholder focus, measurement, analysis and knowledge management, human resource focus and process management. Sum performance score was 80.20 and revealed that leadership, client and stakeholder focus and process management were significantly correlated with the Nongbualamphu Rehabilitation Fund performance score (p <0.05). Conclusion: The self assessment demonstrated good level of the Nongbualamphu Rehabilitation Fund overall performance score. Leadership, client and stakeholder focus and process management are factors that significantly correlated with the performance score.